2018
DOI: 10.1017/s0021932018000366
|View full text |Cite
|
Sign up to set email alerts
|

Differences in prevalence and determinants of hypertension according to rural–urban place of residence among adults in Bangladesh

Abstract: This cross-sectional study analysed Bangladesh Demographic and Health Survey 2011 data with the aim of investigating the prevalence of, and risk factors for, hypertension in individuals aged over 35 by rural–urban place of residence. After estimation of the stratified prevalence of hypertension by background characteristics, multivariable logistic regression analysis was conducted to calculate the adjusted odds (AORs) and 95% confidence intervals (CIs) for selected factors. Of the 7839 participants, 1830 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 42 publications
3
28
1
Order By: Relevance
“…This study conducted from 2015 to 2017 provided the updated current status of hypertension in northern China, with a prevalence of 54.5% among women and 57.4% among men. The prevalence of hypertension in the present study was higher than that reported in most other parts of China 13,14,22 and higher than the rates in many other countries 20,[23][24][25][26] . Lu et al also reported a prevalence of 43.3% among women and 46.9% among men in a representative Chinese population aged 35-75 years, during 2014-2017 10 .…”
Section: Discussioncontrasting
confidence: 85%
“…This study conducted from 2015 to 2017 provided the updated current status of hypertension in northern China, with a prevalence of 54.5% among women and 57.4% among men. The prevalence of hypertension in the present study was higher than that reported in most other parts of China 13,14,22 and higher than the rates in many other countries 20,[23][24][25][26] . Lu et al also reported a prevalence of 43.3% among women and 46.9% among men in a representative Chinese population aged 35-75 years, during 2014-2017 10 .…”
Section: Discussioncontrasting
confidence: 85%
“…This finding is coherent with a Bangladeshi study, which revealed that highly educated urban and rural respondents had higher odds of developing hypertension. 14 On the other hand, an opposite trend was observed in developed countries, where less educated people are more prone to develop hypertension. 47 48 Highly educated people from a developing country might be habituated to perform less physical activity and consume a higher quantity of unhealthy food items such as red meat and processed food.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study used data from the Bangladesh Demographic and Health Survey 2010, which did not include data on behavioural risk factors e.g., fruits and vegetable consumption, physical activity and tobacco consumption. 14 Therefore, we conducted this analysis to measure the difference in prevalence of hypertension and its associated risk factors in urban and rural areas of Dhaka division using data from the Strengthening Health Systems through Organizing Communities (SHASTO) project baseline survey. The government of Bangladesh, together with the Japan International Cooperation Agency (JICA), is implementing the SHASTO project for improving NCD, maternal, newborn and child health services in an integrated manner in Dhaka city and Narsinghdi district.…”
Section: Introductionmentioning
confidence: 99%
“…Another nationally representative analysis conducted in 2011 among adults ≥35 years found the age-standardised prevalence of hypertension and prehypertension was 24.4% and 27.1%; the odds of having hypertension were higher among women compared with men 18 in both urban and rural regions. 19 In one study conducted in rural Bangladesh, the prevalence of hypertension was 16% and factors such as increasing age and higher BMI was positively associated with hypertension. 10 Although they found no difference in prevalence of hypertension by sex, the prevalence of prehypertension was higher among men (33.6%) than women (30.6%), which is similar to our findings.…”
Section: Discussionmentioning
confidence: 99%